2017
DOI: 10.1007/s00056-017-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined orthodontic-orthognathic treatment for class II and III correction on posterior airway space

Abstract: Bignathic surgery led to smaller changes of pharyngeal depth in Class II and III patients than monognathic surgery. Alterations of the PAS due to orthognathic surgery should be considered during orthodontic and presurgical treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…Twenty papers were finally included in the SR 32‐51 . The data extracted from the included papers are reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty papers were finally included in the SR 32‐51 . The data extracted from the included papers are reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty papers were finally included in the SR. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] The data extracted from the included papers are reported in Table 2. The number of subjects included in the studies ranged from 15 to 102, with a total number of 617 Class II adult individuals treated with SMA.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basierend auf der vorstehend von Fransson et al [7] publizierten Messmethodik, inaugurierten Kinzinger et al [8] eine Messmethodik, die 6 Ebenen umfasste (▶ Abb. 1) und seither in weiteren Untersuchungen verwendet wurde [9,10].…”
Section: Extrathorakaler Luftraum -Definitionenunclassified
“…Moreover, results from a meta-analysis showed that adjunct orthodontic treatments, such as rapid maxillary expansion, do not affect the airway below the palatal plane [ 7 ]. Based on the previous literate [ 5 , 6 , 7 , 8 ], it is evident that there is a lack of consensus regarding the influence of fixed OT on PAS dimensions following the correction of skeletal class-II and -III malocclusion.…”
Section: Introductionmentioning
confidence: 99%